Service quality delivery and its impact on customer satisfaction in the bank services in Tanzania: The case of Moshi Uchumi Commercial Bank - Shanghali, John Wifred (Mzumbe University, 2025)
A dissertation submitted in fulfillment of the requirements for the award of the degree of Master of Business Administration (MBA-CM) of Mzumbe University